ANALYSIS OF BRAKING SENSOR SYSTEM IN FLOUR PACKAGING TRANSPORT AT PT X - Yosua Davidson; Haris Abizar (Universitas Muhammadiyah Tangerang, 2026)
This research aims to analyse the effectiveness and workings of the safety sensor system in the transportation of 25 kg flour packaging at PT X. The research method used is a case study with a qualitative approach through observation, interviews, and descriptive data analysis. The focus of the research includes the conveyance of the results of the 25 kg flour packing process and understanding the basic mechanisms and functions of the conveyor system with infrared sensors and PLC interlocks in the 25 kg flour packaging process to ensure safety and operational efficiency. The results show that the safety sensor system integrated with PLC plays an important role in detecting the presence of products, regulating the movement of the conveyor, and ensuring product safety from metal contamination. The interlock system enables real-time control and monitoring of the product transfer process, as well as providing alerts in case of problems. This research is expected to contribute to the logistics and food industry in improving product safety and quality through sensor system optimisation, monitoring system integration, early warning system development, regular evaluation and maintenance, and operator training.Â